Functional association of a CD40 gene single-nucleotide polymorphism with the pathogenesis of coronary heart disease. Issue 6 (2nd August 2019) - Sultan, Cheryl S; Weitnauer, Michael; Turinsky, Martin; Kessler, Thorsten; Brune, Maik; Gleissner, Christian A; Leuschner, Florian; Wagner, Andreas H; Hecker, Markus
Abstract: Aims: Endothelial dysfunction is a major contributor to the pathogenesis of atherosclerosis. CD40–CD40 ligand interactions confer a pro-inflammatory phenotype to endothelial cells (ECs). Recently, a thymine to cytosine transition (−1T>C) in the Kozak sequence of the CD40 gene (rs1883832) has been associated with coronary heart disease (CHD) in an Asian population. As there are no reports yet regarding its role in other ethnic groups, this study determines if the −1T>C single-nucleotide polymorphism (SNP) could be a risk factor for CHD in Caucasians by performing an association study and elucidates its functional consequence in cultured ECs. Methods and results: Molecular and biochemical techniques, cell adhesion assays were used for genotype-stratified human EC characterization. SNP distribution in Caucasians was examined in a hospital-based case–control CHD study and serum levels of soluble CD40 (sCD40) were quantified by ELISA. The SNP in the CD40 gene affected baseline CD40 protein abundance on ECs. There was a genotype-dependent difference in CD40-mediated expression of pro-inflammatory genes. Monocyte adhesion was highest on the surface of cells homozygous for the C allele. Homozygosity for the C allele was associated with significant 2.32-fold higher odds of developing CHD as compared to TT genotype carriers. sCD40 plasma levels were genotype-dependently elevated in CHD patients, indicating a possible prognostic value. Conclusion: The C allele of the CD40 SNP provokes a pro-inflammatory EC phenotype, compensated by an enhanced CD40 shedding to neutralize excess CD40 ligand. Homozygosity for the C allele is the cause for a genetic susceptibility to atherosclerosis and its sequelae. Graphical Abstract: